2022
DOI: 10.3389/fimmu.2022.901176
|View full text |Cite
|
Sign up to set email alerts
|

Serum multi-cytokines screening identifies TRAIL and IL-10 as probable new biomarkers for prostate health index diagnostic utility adjustment in grey zone aggressive prostate cancer detection: A single-center data in China

Abstract: ObjectiveTo identify less invasive and easily applicable serum cytokine-derived biomarkers which contribute to the diagnostic utility and risk assessment ability of the prostate health index (PHI) based multivariable model in grey zone aggressive prostate cancer (AG PCa) early detection.MethodsSerum 45 cytokines screening was performed in a small training cohort consisting of 10 sera by Luminex liquid array-based multiplexed immunoassays and identified TRAIL and IL-10 as new biomarkers for PHI diagnostic utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…For instance, Luminex’s liquid array-based multiple immunoassay was used in aggressive prostate cancer to screen serum cytokines and identify less invasive and easily applicable serum cytokine-derived biomarkers. Serum TRAIL and IL-10 were identified as new biomarkers for prostate cancer detection and risk stratification ( 45 ). In addition, some articles have reported the characterization of soluble molecules in malignant tumors ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Luminex’s liquid array-based multiple immunoassay was used in aggressive prostate cancer to screen serum cytokines and identify less invasive and easily applicable serum cytokine-derived biomarkers. Serum TRAIL and IL-10 were identified as new biomarkers for prostate cancer detection and risk stratification ( 45 ). In addition, some articles have reported the characterization of soluble molecules in malignant tumors ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation by Faupel-Badger et al revealed a relationship between IL-10 and PCa risk and disease severity [109]. In addition, IL-10 has been identified as a potential new biomarker for PCa in the most recent study of serum multicytokines screening [110]. P13K in the CRPC xenograft increased the expression of IL-10 in the blood, but voluntary wheel running may decrease this expression [111].…”
Section: Il-9 Il-10 and Il-11 And Pcamentioning
confidence: 99%
“…Although most (10/24) were based on a quantitative Polymerase Chain Reaction (qPCR) [42,44,[47][48][49][50][51][52][53]64], six used mass-spectrometry technology [54,[56][57][58]60,61], two analyzed the biomarkers using Nanostring [43,65], and one used Nanostring and ELISA together [46]. Digital PCR [45], chemical analysis [59], haemocytometer and fluorescence microscopy analyses [55], nanoscale flow cytometer [62], and Luminex cytokine immunoassays [63] were reported by one study each.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Lastly, Koo and colleagues reported a panel composed of one mRNA, one miRNA, and one long non-coding RNA (lncRNA) (TMPRESS2:ERG, miR-107 and SChLAP1) [53] as potential risk biomarkers. Among these studies, thirteen based their approach on urine samples [43,44,[46][47][48][51][52][53]56,57,61,64,65], five on plasma [42,45,50,59,62], four on serum [54,58,60,63], and only one used whole blood [55] and semen [49]. Although most (10/24) were based on a quantitative Polymerase Chain Reaction (qPCR) [42,44,[47][48][49][50][51][52][53]64], six used mass-spectrometry technology [54,[56][57][58]60,61], two analyzed the biomarkers using Nanostring [43,65], and one used Nanostring and ELISA together [46].…”
Section: Literature Overviewmentioning
confidence: 99%